2012
DOI: 10.1111/j.1528-1167.2012.03437.x
|View full text |Cite
|
Sign up to set email alerts
|

Early onset West syndrome with severe hypomyelination and coloboma‐like optic discs in a girl with SPTAN1 mutation

Abstract: Recent study has shown that mutations in the alpha-II-spectrin (SPTAN1) gene cause early onset intractable seizures, severe developmental delay, diffuse hypomyelination, and widespread brain atrophy. We report a Slovene girl with hypotonia, lack of visual attention, early onset epileptic encephalopathy, and severe developmental delay. The patient presented with segmental myoclonic jerks at the age of 6 weeks, and infantile spasms at the age of 3.5 months. Her seizures were resistant to treatment. Multiple elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 12 publications
0
22
0
1
Order By: Relevance
“…SPTAN1 haploinsufficiency has been discovered in a few patients with EIEE as West syndrome with severe hypomyelination and diffuse brain atrophy (Saitsu et al, 2010;Writzl et al, 2012;Nonoda et al, 2013), in a case of ponto-cerebellar hypoplasia and generalized epilepsy (Hamdan et al, 2011), and also in two cases with nonsyndromic intellectual disability without epilepsy (Campbell et al, 2012). The existence of the last two cases, as well as the absence of hypomyelination in patients with SPTAN1 deletion, has given rise to the hypothesis that SPTAN1 haploinsufficiency alone may not necessarily lead to an epileptic phenotype, and that a less deleterious effect may be associated with loss-of-function mutations (i.e., deletions) as compared to a potential dominant negative or gain-of-function effect related to in-frame SPTAN1 mutations (Campbell et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…SPTAN1 haploinsufficiency has been discovered in a few patients with EIEE as West syndrome with severe hypomyelination and diffuse brain atrophy (Saitsu et al, 2010;Writzl et al, 2012;Nonoda et al, 2013), in a case of ponto-cerebellar hypoplasia and generalized epilepsy (Hamdan et al, 2011), and also in two cases with nonsyndromic intellectual disability without epilepsy (Campbell et al, 2012). The existence of the last two cases, as well as the absence of hypomyelination in patients with SPTAN1 deletion, has given rise to the hypothesis that SPTAN1 haploinsufficiency alone may not necessarily lead to an epileptic phenotype, and that a less deleterious effect may be associated with loss-of-function mutations (i.e., deletions) as compared to a potential dominant negative or gain-of-function effect related to in-frame SPTAN1 mutations (Campbell et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Human mutations in ␣II spectrin cause West syndrome, a severe infantile epilepsy that includes seizures, hypomyelination, and brain atrophy (Saitsu et al, 2010;Writzl et al, 2012;Tohyama et al, 2015). Mice and zebrafish lacking ␣II spectrin are embryonic and larval lethal due to cardiac and nervous system malformations (Voas et al, 2007;Stankewich et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in a study in which exome sequencing was performed in 264 patient-parent trios with EE, de novo mutations were recurrently observed in probands within known causative genes for West syndrome, such as STXBP1 (n = 4) and CDKL 5 (n = 2) 9 . In other recent studies, de novo mutations in GRIN2B 10 , GNAO1 11 , KCNT1 12 and SPTAN1 13 found in probands have been recognized as being associated with West syndrome. These findings showed that West syndrome is a genetically heterogeneous condition, and de novo mutations play a significant role in the onset of West syndrome.…”
Section: Introductionmentioning
confidence: 91%